Evaluating the efficiency of technical equipmentin transport holding company units - Tereshina, Natalya; Podsorin, Victor; Bogdanova, Tatyana; Zavyalova, Nadezhda (Opción, 2019)
The study aims to investigate the efficiency of technical equipment in transport holding company units. The proposed methodological approach to evaluating the efficiency of technical equipment in the transport holding company helps detect provisions for improving the efficiency of the holding company’s productive capacity rather than that of its business units. As a result, the proposed methodology for determining capital productivity fosters the development of a coherent policy. In conclusion, it is necessary to devise an appropriate system for reporting the performance indicators of business units located in the proximity of railways.